(untitled) (International Journal of Child Health and Nutrition, 2014)
Objective: The main aim of the study was to identify factors contributing to positive deviance in growth of children in rural communities of Northern Ghana. Methods: Weassessed factors contributing to nutritional positive deviance among rural poor households by comparing household feeding care practices and health seeking behaviour in families with normal children (that is, neither stunted nor wasted) with children having at least one form of under nutrition. Results:The prevalence of stunting and wasting was 28.0 % (CI: 25.3 - 30.9), and 10.5 % (CI: 9.0 - 12.3) respectively. Multivariable logistic regression adjusted for cluster sampling showed that positive deviant children (that is, neither wasted nor stunted) were 2.4 times more likely to have taller (≥160 cm) mothers [AOR 2.38; 95% CI (1.83 - 3.10)]. Female children were significantly more likely to be positive deviant [AOR 1.44; 95% CI (1.17 - 1.77)]. Households using salt of adequate iodine content were more likely to have positive deviant children [AOR 1.36; 95% CI (1.03 - 1.80)]. Conclusion and Recommendation:Positive deviance in child growth was characterized by taller mothers, being a female child, high maternal nutrition knowledge and being resident in the Upper West Region. The persistent high levels of child under nutrition in Northern Ghana can be mediated through a sustainable focused intervention strategy to improve maternal nutrition.